The scanning four‐bounce monochromator for beamline I20 at the Diamond Light Source. (2nd August 2018) - Hayama, Shusaku; Duller, Graham; Sutter, John P.; Amboage, Monica; Boada, Roberto; Freeman, Adam; Keenan, Luke; Nutter, Brian; Cahill, Leo; Leicester, Pete; Kemp, Ben; Rubies, Nico; et al.
Abstract : A scanning four‐bounce monochromator that offers an unprecedented level of stability in the incident beam energy resolution and calibration has been developed for a flagship spectroscopy beamline at Diamond Light Source. Abstract : A description of the technical and design details of a scanning four‐bounce crystal monochromator that has recently been commissioned for the Versatile X‐ray Absorption Spectroscopy (XAS) beamline at Diamond Light Source is presented. This device consists of two independent rotary axes of unique design which are synchronized using a multiple read‐head encoder system. This monochromator is shown to be capable of maintaining the flux throughput of the Bragg axes without the need of any external feedback mechanism from 4 to 20 keV. The monochromator is currently equipped with cryogenically cooled crystals with the upstream axis consisting of two independent Si(111) crystals and a pair of channel‐cut crystals in the downstream axis. The possibility of installing an additional Si(311) crystal‐set to extend the energy range to 34 keV is incorporated into the preliminary design of the device. Experimental data are presented showing the exceptional mechanical stability and repeatability of the monochromator axes.